2022
DOI: 10.1136/bmjopen-2022-068313
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy, cognitive effects and acceptability of electroconvulsive therapies for the treatment of depression: protocol for a systematic review and network meta-analysis

Abstract: IntroductionThere have been important advances in the use of electroconvulsive therapy (ECT) to treat major depressive episodes. These include variations to the type of stimulus the brain regions stimulated, and the stimulus parameters (eg, stimulus duration/pulse width). Our aim is to investigate ECT types using a network meta-analysis (NMA) approach and report on comparative treatment efficacy, cognitive side effects and acceptability.MethodWe will conduct a systematic review to identify randomised controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…As discussed in more detail in our prior publication (see [ 21 ]), although this excitatory pro-neurogenic activity is traditionally considered beneficial, one could not exclude the possibility that seizures might generate misplaced neurons with irregular morphological and electrophysiological features, such as the ones observed in epileptic rodent models, a process described as aberrant neurogenesis (e.g., [ 52 , 53 ]), and whose functions stills need to be defined. In fact, since newly generated proliferating cell and neural progenitors were only partially needed for ECS' antidepressant-like response to occur (see [ 21 ]), the changes induced by ECS might contribute to other roles in the hippocampus (see [ 54 ]), such as promoting structural plasticity (e.g., reviewed by [ 55 ]), gliogenesis [ 56 ], synaptogenesis (e.g., [ 57 ]) and angiogenesis [ 58 ], that might even be mediating some of the long-term consequence induced by ECS (e.g., [ 14 ]), and that deserve further characterization. Overall, the present data, together with our prior study [ 21 ], report that different dose-intensities of ECS modulated hippocampal neurogenesis in a comparable fashion with age (i.e., decreased cell proliferation observed 8 days post-treatment for adolescent rats, and expected 15 days post-treatment for adults; increased survival of neural progenitors 8 days post-treatment).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in more detail in our prior publication (see [ 21 ]), although this excitatory pro-neurogenic activity is traditionally considered beneficial, one could not exclude the possibility that seizures might generate misplaced neurons with irregular morphological and electrophysiological features, such as the ones observed in epileptic rodent models, a process described as aberrant neurogenesis (e.g., [ 52 , 53 ]), and whose functions stills need to be defined. In fact, since newly generated proliferating cell and neural progenitors were only partially needed for ECS' antidepressant-like response to occur (see [ 21 ]), the changes induced by ECS might contribute to other roles in the hippocampus (see [ 54 ]), such as promoting structural plasticity (e.g., reviewed by [ 55 ]), gliogenesis [ 56 ], synaptogenesis (e.g., [ 57 ]) and angiogenesis [ 58 ], that might even be mediating some of the long-term consequence induced by ECS (e.g., [ 14 ]), and that deserve further characterization. Overall, the present data, together with our prior study [ 21 ], report that different dose-intensities of ECS modulated hippocampal neurogenesis in a comparable fashion with age (i.e., decreased cell proliferation observed 8 days post-treatment for adolescent rats, and expected 15 days post-treatment for adults; increased survival of neural progenitors 8 days post-treatment).…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy, safety and applicability of current ECT practices are the result of a series of improvements in treatment delivery, which have focused on preserving and improving efficacy (e.g., by adjusting ECT electrical dose, stimulus parameters and/or electrode placement), while minimizing the potential cognitive side effects (e.g., [ 13 , 14 ]). Moreover, these parameters have to be adjusted by age and sex, since previous studies reported variations in the electrical charge needed to induce an effective convulsion (e.g., [ 15 19 ]): for example, women seem to require less charge than men of the same age to induce an optimal seizure, and for both sexes the charge needs to be increased with age (e.g., [ 20 ]).…”
Section: Introductionmentioning
confidence: 99%
“…3 To provide some further guidance, a network meta-analysis, attempting to provide a ranking of various ECT "protocols" according to their comparative antidepressant efficacy and cognitive side-effect profile, is currently underway. 9 One possibility is that we will eventually have a clear hierarchy of switching strategies. Alternatively, the evidence might be to continue with the same initial technique, offering a longer course.…”
mentioning
confidence: 99%
“…Of some help is that Hart et al's study indicates that switching to brief pulse unilateral ECT is helpful if not meeting a response criterion after five sessions of ultrabrief pulse ECT 3 . To provide some further guidance, a network meta‐analysis, attempting to provide a ranking of various ECT “protocols” according to their comparative antidepressant efficacy and cognitive side‐effect profile, is currently underway 9 …”
mentioning
confidence: 99%
“…Such costs are attributed to increased unemployment, disability, and reduced work performance ( 9 ). Disturbingly, over 10% of depressed individuals experience suicidal thoughts, with some expressing intention to act ( 10 ), leading to a lifetime suicide rate ranging from 3.8 to 7.8% ( 11 ). More alarmingly, studies have projected that by 2030, depression will become the most common disabling condition in the world, ranking as the second leading cause of disability ( 2 , 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%